Dispute Resolution Institutions and Strategic Militarization - Meirowitz, Adam; Morelli, Massimo; Ramsay, Kristopher W.; Squintani, Francesco (Journal of Political Economy, 2019)
Engagement in a destructive war can be understood as the “punishment” for entering into a dispute. Institutions that reduce the chance that disputes lead to war make this punishment less severe. This may incentivize hawkish policies like militarization and potentially offset the benefits of peace brokering. We study a model in which unmediated peace talks are effective at improving the peace chance for given militarization but lead to more militarization and ultimately to a higher incidence of war. Instead, a form of third-party mediation inspired by work of Myerson effectively brokers peace in emerged disputes and also minimizes equilibrium militarization.